STRATEGI PEMASARAN CABAI (Capsicum annum L.) DALAM UPAYA MENINGKATKAN VOLUME PENJUALAN DI PASAR INDUK PARE KABUPATEN KEDIRI - Elisabeth Dwina Steinela; Erna Haryanti Koestedjo; Koesriwulandari Koesriwulandari (Jurnal Ilmiah Sosio Agribis, 2022)
This study aims to analyze the internal factors and external factors as well as analyze the marketing strategy of the chili business at the Pare Kediri Central Market. Data analysis was carried out by identifying internal factor evaluation (IFE) and external factor evaluation (EFE), determining the appropriate strategy through the IE matrix and SWOT matrix. The results of the study found that internal factors influenced the marketing of chili businesses at the Pare Kediri Main Market. External factors that had an influence were the existence of partnerships between farmers, traders and industry players to expand the marketing network as an opportunity in chili business marketing while the chili payment system used a hanger system which is a threat to chili traders. Judging from the results of the analysis of IFAS and EFAS factors using the SWOT quadrant matrix, the marketing strategy for the chili business is in quadrant I, which means that this condition has a positive meaning to continue marketing the chili business at the Pare Central Market, Kediri. By paying attention to the several SO strategies that have been prepared, one of the right strategies is to expand the marketing and distribution of chili commodities by utilizing social media technology to increase sales volume inside and outside the Kediri Pare Central Market in a sustainable manner.Keywords: Chili, Marketing Strategy, SWOT